A systematic review of factors that predict and mediate conceptual change - Olaogun, Olanrewaju P.; Hunsu, Nathaniel J. (European journal of psychology of education, 2025)
Students have misconceptions about many scientific topics they encounter in the classroom—such misconceptions are especially rife in subjects with counterintuitive concepts. Several studies have copiously documented students’ misconceptions in different science domains. Research shows that students’ misconceptions can be resistant to change and that instructional efforts that facilitate conceptual change learning must intentionally target and refute students’ misconceptions. Several studies have highlighted different factors that foster or inhibit conceptual change learning. This systematic review of conceptual change studies synthesizes the literature to identify factors that predict and mediate conceptual change learning. The systematic review is based on the analysis of 14 studies that satisfied the criteria for inclusion in this review. The findings from this review show that mastery goals, situational interest, and enjoyment were significant predictors of conceptual change. Additionally, deep cognitive engagement, deep processing strategies, and attention allocation were significant mediators of conceptual change. The implications of these observations for theory and instructional practices for instructions that foster conceptual change learning are discussed. This systematic review is important because it can serve as the basis for conducting further empirical studies in engineering to help engineering students gain conceptual understanding and abandon their misconceived ideas and notions.